[Walls Around Lake Viti at Askja] - Streng, Evelyn Fiedler (1975)
Photograph of the walls surrounding Lake Viti at Askja. Brown rock walls covered in large, jagged, rock offshoots surround the white lake in the bottom left corner. A line of people walk along the edge of the lake's walls above the rock offshoots. Water pools are visible along the brown and black hills at the top of the photograph.